Endoscopic Treatment and Considerations for a Rare of Killian‐Jamieson Diverticulum: A Case Report - Guoyao Sun; Wen Jia; Zhuo Yang; Jiao Liu; Yong Sun (JGH Open)
ABSTRACT Background Pharyngoesophageal diverticulum, including the most common Zenker's diverticulum, Killian‐Jamieson diverticulum, and the rarer Laimer's diverticulum, require accurate differentiation for proper treatment. This case report explores the endoscopic features and the diagnostic and therapeutic value of endoscopic ultrasound (EUS) in the management of Killian‐Jamieson diverticulum. Case Presentation A 57‐year‐old woman presented with dysphagia for solids over the past three months. Esophagogastroduodenoscopy (EGD) revealed an esophageal diverticulum located below the upper esophageal sphincter. EUS measured the diverticulum to be 1.0 cm by 1.4 cm and confirmed the absence of muscularis propria, thereby ruling out Laimer's diverticulum. The patient underwent flexible endoscopic septum division (FESD) without any adverse events. A barium esophagram three months post‐surgery indicated a left‐sided Killian‐Jamieson diverticulum. Conclusion This case highlights the importance of combining endoscopic features with barium swallow and EUS for accurate diagnosis of Killian‐Jamieson diverticulum. The results suggest that such an integrated diagnostic approach enhances diagnostic accuracy and guides treatment, offering insights into the management of pharyngoesophageal diverticulum.